2005
DOI: 10.1139/f04-169
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of dietary sodium chloride and waterborne copper in rainbow trout (Oncorhynchus mykiss): copper toxicity and sodium and chloride homeostasis

Abstract: Juvenile rainbow trout (Oncorhynchus mykiss) maintained on either low sodium chloride (LS (control), 1.4% NaCl) or high sodium chloride (HS, 11% NaCl) diet were exposed to 55 µg·L -1 waterborne copper (Cu) for 28 days. Cu-exposed fish maintained on the LS diet exhibited 26% mortality, more than double (11%) that in fish maintained on the HS diet. Waterborne Cu exposure inhibited growth by 56% in fish maintained on the LS diet and by 35% in those maintained on the HS diet. Whole-body and tissue Na + levels, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…2a, b), suggesting that circulatory Na loss is a potential noninvasive indicator of chronic Cu toxicity. This is consistent with our earlier study (Kamunde et al 2005) in which a decline in plasma Na was not only associated with elevated Cu but also with increased mortality and reduced growth. In the current study mortality and growth inhibition did not occur (data not shown) possibly because of the lower Cu exposure concentration (40 vs. 55 lg/L) and different water chemistries.…”
Section: Results and Dicussionsupporting
confidence: 93%
“…2a, b), suggesting that circulatory Na loss is a potential noninvasive indicator of chronic Cu toxicity. This is consistent with our earlier study (Kamunde et al 2005) in which a decline in plasma Na was not only associated with elevated Cu but also with increased mortality and reduced growth. In the current study mortality and growth inhibition did not occur (data not shown) possibly because of the lower Cu exposure concentration (40 vs. 55 lg/L) and different water chemistries.…”
Section: Results and Dicussionsupporting
confidence: 93%
“…The protective effect of waterborne chloride against nitrite toxicity has been attributed to competitive inhibition of nitrite uptake by the chloride cells at the gills (Lewis and Morris 1986). Dietary NaCl can increase the resistance of fish to the toxic effects of some waterborne cations, such as copper in rainbow trout (Kamunde et al , 2005Pyle et al 2003). Kamunde et al (2005) concluded that in rainbow trout fed with dietary NaCl, decreased susceptibility to the toxic effects of waterborne copper was due to an increase in plasma sodium.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary NaCl can increase the resistance of fish to the toxic effects of some waterborne cations, such as copper in rainbow trout (Kamunde et al , 2005Pyle et al 2003). Kamunde et al (2005) concluded that in rainbow trout fed with dietary NaCl, decreased susceptibility to the toxic effects of waterborne copper was due to an increase in plasma sodium. The authors suggest the rise in plasma sodium concentration reduced the efflux of sodium by inhibition of the branchial sodium uptake route, which is also shared by copper.…”
Section: Discussionmentioning
confidence: 99%
“…(2002) reported a time course of <30 s for Na transfer from the gills to the blood; thus, it is plausible that [Na] transfer through the gut could be equally rapid. Alternatively, gut Na could have been lower than the other tissues as a result of having starved the fish for 36 h prior to sampling, as sampling after a period of starvation may not reveal the apparently transient changes in tissue Na levels that occur (Kamunde et al ., 2004). In contrast, Pyle et al .…”
Section: Discussionmentioning
confidence: 99%